2023
DOI: 10.1177/02656590231202177
|View full text |Cite
|
Sign up to set email alerts
|

Explicit cognate instruction facilitates vocabulary learning by foreign language learners with developmental language disorder

Elena Tribushinina,
Geke Niemann,
Joyce Meuwissen

Abstract: This article is one of the first attempts to study the mechanisms of foreign language learning by children with DLD. We test the effectiveness of a cognate intervention aiming to enhance cross-linguistic awareness of Dutch-speaking primary-school pupils with DLD, as part of their English as a Foreign Language (EFL) curriculum. The participants were learning English as a school subject in the last three years of special primary education in the Netherlands (ages 8;11–13;8). The intervention group ( n = 41) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Although our study only included a business-as-usual curriculum, there are reasons to assume that the lack of progress was (at least partly) due to the implicit teaching approach, which did not include explicit explanation of grammar rules or cross-language comparisons. These results are in line with the prior findings for primary-school children with DLD, demonstrating that pupils with DLD do not make progress in EFL skills if their English curriculum is implicit and skill-based (Tribushinina et al, 2022(Tribushinina et al, , 2023b. According to Ullman and Pierpont (2005), procedural learning is impaired in children with DLD.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although our study only included a business-as-usual curriculum, there are reasons to assume that the lack of progress was (at least partly) due to the implicit teaching approach, which did not include explicit explanation of grammar rules or cross-language comparisons. These results are in line with the prior findings for primary-school children with DLD, demonstrating that pupils with DLD do not make progress in EFL skills if their English curriculum is implicit and skill-based (Tribushinina et al, 2022(Tribushinina et al, , 2023b. According to Ullman and Pierpont (2005), procedural learning is impaired in children with DLD.…”
Section: Discussionsupporting
confidence: 90%
“…Metalinguistic approaches to both vocabulary and grammar teaching appear even more vital in foreign language teaching to children with DLD because in this case the deficits are aggravated by limited exposure. Tribushinina et al (2022Tribushinina et al ( , 2023b compared EFL learning gains in Dutch-speaking primary-school children with DLD (age 9-12) following either a business-as-usual curriculum (implicit) or an explicit intervention raising metalinguistic and cross-linguistic awareness. Their results revealed significant progress in the intervention group after 12 weeks of explicit vocabulary (Tribushinina et al, 2023b) and grammar (Tribushinina et al, 2022) instruction, but no progress was observed in the business-as-usual group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the rich literature on FL learning by typicallydeveloping pupils, there are only a few studies focusing on pupils with DLD learning English as a school subject (Zoutenbier and Zwitserlood, 2019;Tribushinina et al, 2020Tribushinina et al, , 2022Tribushinina et al, , 2023aStolvoort et al, 2023). Their findings suggest that pupils with DLD learn English slower and attain lower scores than peers without DLD (Zoutenbier and Zwitserlood, 2019;Tribushinina et al, 2020), even though their EFL learning can be enhanced by using teaching methods tailored to the specific needs of this population (Tribushinina et al, 2022(Tribushinina et al, , 2023bStolvoort et al, 2023).…”
Section: Developmental Language Disorder and Foreign Language Learningmentioning
confidence: 99%